Distribution Of Lightweight File Delivery Using IoT - Tanjung, Anggi Muhammad; Pardede, A M H (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2023)
A lightweight file lifter car distribution device using Iot has been designed. This robot system uses the NodeMCU ESP8266 microcontroller where the NodeMCU ESP8266 functions as a data processor, and also a WI-FI network receiver emitted by a WI-FI network system. This robot car system uses a control system using an Android smartphone to control the movement of the wheels, this robot car uses a WI-FI network communication system so that the robot car system and Android smartphone can be connected, in this robot car system it uses a DC motor rotation direction drive driver which is The driver functions to move the direction of rotation of the DC motor on the wheels of the robot car. The power supply for this robot uses 3 3.7 Volt Li-Ion batteries which are arranged in series to get a 12 volt voltage, the 12 volt battery voltage goes first to the 7805 regulator IC circuit to get an output voltage of 5 volts, 5 volts voltage. this is what functions to supply the robot system so that it can be operated